Genre et Soin - Anne Marie Moulin (Arabian Humanities)
Nursing is at the core of the modern health system and has developed in all countries of the Arabian Peninsula. The profession suffers from a chronic lack of local womanpower and countries rely heavily on immigrant nurses. The socio-anthropological status of professional nursing raises two questions: nursing implies being in contact with human bodies, and a relationship between men and women that is normally restricted outside the family sphere, two issues fundamental for the regulation of social life, according to tradition and to religion. These issues did not go unnoticed in the West, where countries have elaborated their own solutions and keep working at them. Based on literature and my own empirical experiences, this article shows the nurse’s status as a critical point for the safety of the health system and the work of the medical team and as a touchstone for the transformation of gender in the region in the years to come.